Фронтир як категорія кримінологічного дискурсу - Орлов, Ю. В.; Orlov, Y. V.; Орлов Юрій Володимирович (Архів кримінології та судових наук. - 2020. - № 1. - С. 98-108, 2020)
Конвергенція тенденцій глобалізації та глокалізації у розвитку світу загалом та різного масштабу соціальних груп у межах окремих держав, зокрема, подальша фрагментація та капсуляція наративів, дискурсивних систем актуалізує кримінологічну проблематику фронтирів. Мета статті полягає у виявленні, описі й поясненні змісту категорії «фронтир» як елементу кримінологічного дискурсу. Установлено, що фронтири є зонами соціокультурного зіткнення, активної взаємодії контроверсійних цивілізаційних зразків із претензійністю на домінування, експансію та захист. Ці позиції та установки соціальної діяльності часто реалізуються у кримінальних формах, що ставить на порядок денний питання про вивчення сутності фронтирної злочинності, розробку заходів зниження факторів її детермінації, зокрема ресентименту.

The significance of frontiers has been actualizing in the modern world as border zones, in which there is a diffusion of social and group differences, interaction of cultures, narratives, clash of civilizations. These areas are filled with conflicts of diverse nature, genesis, reproduction of which often contains significant criminogenic potential, manifested frontal crime. They have not as much a physical spatial, geographical, as a socio-temporal dimension, the spaces of existence of which unfold in the sphere of discourse, thinking, and are provided with an extensive, global telecommunication infrastructure. The purpose of the article is to establish, describe and explain the content of the category «frontier» as an element of criminological discourse. The frontier is defined as a border and borderzone between cultures, epochs in the actual calendar, physical time; it is a place of active interaction, clash of civilizations, cultures; the opposition, determined by the state of struggle, implicitly presupposes expansion and protection, a state of hostility, anxiety, and sacrifice. Frontier crime is a type of crime determined by conflicts in the area of social frontiers. Specific evidence of committing frontal crime: 1) it’s a conflict of identities; 2) has a political and/or religious motivation, however security-dominant and solidarity motivation; 3) aggressive and violent in nature; 4) depends on historical and/or religious-dogmatic (fundamentalist) consciousness, relies on the mechanisms of postmemory, radicalized discourse, actualized memes, symbols. In the global dimension, the implementation of frontal crime is explained by the mechanisms of the development of conflict between cultures. In the national – there have been identified three types of frontier crime: transitive, immanent, and postmodern anomie. Operating the frontier as a category of criminological discourse provides opportunities for a deeper study of the determination of political crime in Ukraine, as well as for the development of strategies for general social development (including in the context of combating crime) taking into account the socio-cultural frontier. Perspective areas of criminological research of the frontier is the study of the influence of the border and cross-border on the promotion of extremism, terrorism, taking into account its importance while designing and implementing the concept of transitional justice, as well as the peculiarities of constitution of frontier identity as an anti-criminal basis.

Конвергенция тенденций глобализации и глокализации в развитии мира в целом и разного масштаба социальных групп в рамках отдельных государств, в частности, дальнейшая фрагментация и капсуляция нарративов, дискурсивных систем актуализирует криминологическую проблематику фронтира. Цель статьи заключается в выявлении, описании и объяснении содержания категории «фронтир» как элемента криминологического дискурса.
Фронтир как категория криминологического дискурса
Frontier as a category of criminological discourse
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; фронтир; соціальний сценарій; наратив; дискурс; символіка; злочинність; ворожнеча; frontier; social scenario; narrative; discourse; symbolism; crime; hostility; социальный сценарий; символика; преступность; вражда